1986
DOI: 10.1056/nejm198609113151102
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Malignant Carcinoid Syndrome

Abstract: We studied the effects of a long-acting analogue of somatostatin (SMS 201-995, Sandoz) in 25 patients with histologically proved metastatic carcinoid tumors and the carcinoid syndrome. This drug was self-administered by subcutaneous injection at a dose of 150 micrograms three times daily. Flushing and diarrhea associated with the syndrome were promptly relieved in 22 patients. All 25 patients had an elevated 24-hour urinary excretion of 5-hydroxyindoleacetic acid (5-HIAA) (mean, 265 mg per 24 hours; range, 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 758 publications
(100 citation statements)
references
References 10 publications
2
97
1
Order By: Relevance
“…Subsequent studies using s.c. octreotide at doses ranging from 50 to 1000 μg, but occasionally up to 3 mg, 2-3 times per day, showed that significant symptomatic improvement of CS was obtained. An analysis of 10 studies that evaluated more than 300 patients with CS treated with s.c. octreotide, with doses ranging between 150 and 3000 μg (median dose 450 μg), showed 70% control of both flushing and diarrhoea (Kvols et al 1986, Vinik & Moattari 1989, Anthony et al 1993, Janson & Oberg 1993, Saltz et al 1993, Arnold et al 1996, di Bartolomeo et al 1996, Rubin et al 1999, O'Toole et al 2000, Aparicio et al 2001. A randomised study comparing daily s.c. injections of short-acting octreotide to octreotide LAR at various doses every 4 weeks demonstrated an at least equivalent symptomatic control (Rubin et al 1999).…”
Section: :9mentioning
confidence: 99%
“…Subsequent studies using s.c. octreotide at doses ranging from 50 to 1000 μg, but occasionally up to 3 mg, 2-3 times per day, showed that significant symptomatic improvement of CS was obtained. An analysis of 10 studies that evaluated more than 300 patients with CS treated with s.c. octreotide, with doses ranging between 150 and 3000 μg (median dose 450 μg), showed 70% control of both flushing and diarrhoea (Kvols et al 1986, Vinik & Moattari 1989, Anthony et al 1993, Janson & Oberg 1993, Saltz et al 1993, Arnold et al 1996, di Bartolomeo et al 1996, Rubin et al 1999, O'Toole et al 2000, Aparicio et al 2001. A randomised study comparing daily s.c. injections of short-acting octreotide to octreotide LAR at various doses every 4 weeks demonstrated an at least equivalent symptomatic control (Rubin et al 1999).…”
Section: :9mentioning
confidence: 99%
“…Long-acting somatostatin analogues as octreotide acetate and lanreotide have been repeatedly shown to improve or even normalize diarrhoea and flushing in patients with carcinoid syndrome [10, 12, 13, 14, 15]during both short- and long-term treatment. Symptom relief is correlated with reduction of hormonal markers.…”
Section: Control Of Symptoms In Patients With Functionally Active Neumentioning
confidence: 99%
“…Several studies have shown promising results in improved symptoms and longevity in patients with carcinoid syndrome. [12][13][14][15][16] However, for patients with cardiac involvement, worsening right-sided heart failure remains a major cause of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%